Psychotherapy Style Scale: Development and Validation - Zhou, Shegang; Hou, Yanfei; Liu, Ding; Xu, Duo; Zhang, Xiaoyuan (Frontiers in Psychology, 2021)
Psychotherapy style is conceptualized as the therapeutic method that a therapist employs while working with clients during treatment. It influences both the therapeutic process and results of therapeutic actions. The present study developed and validated the Psychotherapy Style Scale (PSS). By following a systematic psychometric development process, a three-factor structure of the PSS was identified. Exploratory factor analysis and confirmatory factor analysis provided evidence of multidimensional structure and validity of the PSS. Cronbach's a suggested that the resulting scale was highly reliable. Criterion validity was also satisfactory, demonstrated by correlations between the scale and criterion validity measures. The PSS has the potential to help better understand therapists' behavioral characteristics and select the most appropriate therapists for clients who undergo psychotherapy.